PERAN SERTA MASYARAKAT DALAM PEMBANGUNAN - I Putu Gede Ardhana (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science))
Community’s participation in development has been made since the enactment of 1945Constitution and constitutionally it has clear reference and it becomes the obligation ofanybody involved in the management of natural resources in Indonesia. However theparticipation of the community in the development in the reform era has shown the tendencyof running imperfectly. What is the condition of the community’s participation from thebeginning up to now does not yet have clear position in the form of authority and obligationand the right as community in making their participation in running the government is put intoa study. The method employed for the study is library research by using secondary datacoming from literatures, mass media, the specifications of legislations; comperative study wasalso made from various opinions and the understanding of community’s participation. Anumber of variables to be studied among others are: the specification of legislation, role ofgovernment, form of interaction of the implementation of community’s participation, andefforts made by the government within the context of community’s participation so thatdevelopment can be increased. From the study of the implementation of the legislationsinvolving community’s participation since old order until the regional autonomy era it has notyet run effectively and efficiently.